Lower bone turnover and relative bone deficits in men with metabolic syndrome: a matter of insulin sensitivity? The European Male Ageing Study. Issue 11 (November 2016) - Laurent, M.; Cook, M.; Gielen, E.; Ward, K.; Antonio, L.; Adams, J.; Decallonne, B.; Bartfai, G.; Casanueva, F.; Forti, G.; Giwercman, A.; Huhtaniemi, I.; et al.
Abstract Summary We examined cross-sectional associations of metabolic syndrome and its components with male bone turnover, density and structure. Greater bone mass in men with metabolic syndrome was related to their greater body mass, whereas hyperglycaemia, hypertriglyceridaemia or impaired insulin sensitivity were associated with lower bone turnover and relative bone mass deficits. Introduction Metabolic syndrome (MetS) has been associated with lower bone turnover and relative bone mass or strength deficits (i.e. not proportionate to body mass index, BMI), but the relative contributions of MetS components related to insulin sensitivity or obesity to male bone health remain unclear. Methods We determined cross-sectional associations of MetS, its components and insulin sensitivity (by homeostatic model assessment-insulin sensitivity (HOMA-S)) using linear regression models adjusted for age, centre, smoking, alcohol, and BMI. Bone turnover markers and heel broadband ultrasound attenuation (BUA) were measured in 3129 men aged 40–79. Two centres measured total hip, femoral neck, and lumbar spine areal bone mineral density (a BMD, n  = 527) and performed radius peripheral quantitative computed tomography (pQCT, n  = 595). Results MetS was present in 975 men (31.2 %). Men with MetS had lower β C-terminal cross-linked telopeptide (β-CTX), N-terminal propeptide of type I procollagen (PINP) and osteocalcin (P  < 0.0001) and higher total hip, femoral neck, and lumbar spinea BMD (P  ≤ 0.03). Among MetS components, only hypertriglyceridaemia and hyperglycaemia were independently associated with PINP and β-CTX. Hyperglycaemia was negatively associated with BUA, hypertriglyceridaemia with hipa BMD and radius cross-sectional area (CSA) and stress–strain index. HOMA-S was similarly associated with PINP and β-CTX, BUA, and radius CSA in BMI-adjusted models. Conclusions Men with MetS have highera BMD in association with their greater body mass, while their lower bone turnover and relative deficits in heel BUA and radius CSA are mainly related to correlates of insulin sensitivity. Our findings support the hypothesis that underlying metabolic complications may be involved in the bone's failure to adapt to increasing bodily loads in men with MetS.